Knowledge, attitude, and practice toward hyperuricemia among healthcare workers in Shandong, China - Peng, Honghai; Zhang, Ke; Zhang, Chunxue; Gao, Jun (PeerJ, 2024)
Background Hyperuricemia is a relatively common condition, with a prevalence of over 20% among the general population. Also, most patients initially present no symptoms. This study aimed to investigate the knowledge, attitude, and practice (KAP) toward hyperuricemia among healthcare workers in Shandong, China. Methods Healthcare workers were recruited in this cross-sectional study conducted in Shandong in December 2022. A self-designed questionnaire was used to collect demographic information and KAP data. Results A total of 372 questionnaires were distributed, and 216 (58.06%) valid questionnaires were collected from 131 physicians, 80 nurses, and five other healthcare workers. The participants had a mean score of 10.76 ± 2.53 (possible range: 0–14, 76.9%) and 31.94 ± 2.58 (possible range: 0–40, 79.9%) in knowledge and attitude, respectively. The physicians’ and nurses’ practice scores were 47.57 ± 5.34 (possible range: 0–55, 86.5%) and 30.06 ± 4.11 (possible range: 0–35, 85.9%), respectively. The attitude scores were independently associated with proactive practice in both physicians (P < 0.001) and nurses (P = 0.046). Conclusion This study found that healthcare workers in Shandong had adequate knowledge, positive attitudes, and proactive practices towards hyperuricemia. However, there is room for improvement in the attitudes of both physicians and nurses to achieve better practice.
Keywords: Knowledge; Attitudes; Practice; Hyperuricemia; Cross-sectional study; Gout